Heat Transfer in a Loop Heat Pipe using Diamond-H2O Nanofluid - Gunnasegaran P.; Abdullah M.Z.; Yusoff M.Z.; Kanna R. (Taylor and Francis Ltd., 2023)
Diamonds; Finite volume method; Fluids; Heat pipes; Heat transfer; Laminar flow; Nanoparticles; Flow and heat transfer; Governing equations; Heat transfer and fluid flow; Heat transfer characteristics; Loop heat pipes; Mass concentration; Thermal Performance; Three-dimensional model; Nanofluidics